2015
DOI: 10.3348/kjr.2015.16.5.996
|View full text |Cite
|
Sign up to set email alerts
|

Breast Microcalcifications: Diagnostic Outcomes According to Image-Guided Biopsy Method

Abstract: ObjectiveTo evaluate the diagnostic outcomes of ultrasonography-guided core needle biopsy (US-CNB), US-guided vacuum-assisted biopsy (US-VAB), and stereotactic-guided vacuum-assisted biopsy (S-VAB) for diagnosing suspicious breast microcalcification.Materials and MethodsWe retrospectively reviewed 336 cases of suspicious breast microcalcification in patients who subsequently underwent image-guided biopsy. US-CNB was performed for US-visible microcalcifications associated with a mass (n = 28), US-VAB for US-vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 27 publications
1
22
2
2
Order By: Relevance
“…As given in Table , lesion size greater than or equal to 2 cm, the absence of circumscribed margins, RI greater than or equal to 0.7, and axillary abnormal nodes were found to be significant predictors of malignancy. Although microcalcification is an US imaging characteristic that is important for early diagnosis of breast cancer, we found no association between microcalcification and malignancy in our series of complex cysts. Possible explanations for this result are as follows.…”
Section: Discussioncontrasting
confidence: 84%
“…As given in Table , lesion size greater than or equal to 2 cm, the absence of circumscribed margins, RI greater than or equal to 0.7, and axillary abnormal nodes were found to be significant predictors of malignancy. Although microcalcification is an US imaging characteristic that is important for early diagnosis of breast cancer, we found no association between microcalcification and malignancy in our series of complex cysts. Possible explanations for this result are as follows.…”
Section: Discussioncontrasting
confidence: 84%
“…Currently, close sonographic examination performed by an experienced sonographer using high-resolution probes allows a better visualization of breast microcalcifications [6][7][8][9]. Nonetheless, sonography remains to play a supplementary role in detecting breast microcalcifications as localizing these microcalcifications without mammograph-ORIGINAL ARTICLE ic aid is not always successful [7,10,11]. In our institution, sonography is reevaluated in some localized excision after mammographically guided wire insertion to confirm the direction and depth of the wire.…”
Section: Sonographic Examination For Suspicious Mammographic Microcal-mentioning
confidence: 99%
“…Indeed, the problem in this regard is whether one can retain reliable accuracy. However, a recent study that reviewed over 10,000 diagnostic mammographies reported that only 87 (22%) among the 391 lesions that had suspicious mammographic microcalcifications without associated findings could be percutaneously biopsied by sonography only[10]. Unfortunately, sonography alone seems to have an insufficient reliability in detecting breast microcalcifications until now.To enhance the performance of sonography in localizing breast microcalcifications, there have been attempts at combining USG with other localizing interventions.…”
mentioning
confidence: 99%
“…U drugim studijama našli smo po datke o udjelu malignih nalaza dobivenih biopsijom vođenom mamografski od 21 do 55%. 10,33,36,[49][50][51] Ovi postotci uvelike ovise o vrsti bioptiranih promjena, a u našem materijalu prevladavali su mikrokalcifikati, s čak 74%, dok su tvorbe bile zastupljene sa svega 12% (njih smo bioptirali uglavnom pod kontrolom ultra zvuka), što objašnjava ovakav rezultat. U jedne paci jentice s izrazito malenom promjenom, čiji je nalaz biopsije bio invazivni duktalni karcinom, kirurškim zahvatom nije nađen malignitet.…”
Section: A 3bunclassified